Early growth patterns and cardiometabolic function at the age of 5 in a multiethnic birth cohort: the ABCD study - Vrijkotte Tanja GM; van Eijsden Manon; de Beer Marieke; Gemke Reinoud JBJ (BMC, 2009)
Abstract Background The relation between fetal growth retardation and cardiovascular and metabolic diseases in later life has been demonstrated in many studies. However, debate exists around the potential independent role of postnatal growth acceleration. Furthermore, it is unknown whether a potential effect of growth acceleration on cardiovascular and metabolic function is confined to certain timeframes. The present study assesses the (predictive) role of prenatal and postnatal growth on 5 components of cardiovascular and metabolic function in children aged 5. The potential association of timing of postnatal growth acceleration with these outcomes will be explored. Methods and design Prospective multiethnic community-based cohort study of 8266 pregnancies (Amsterdam Born Children and their Development, ABCD study). Up till now, anthropometry of 5104 children from the original cohort was followed during the first 5 years of life, with additional information about birth weight, pregnancy duration, and various potential confounding variables. At age 5, various components of cardiovascular and metabolic function are being measured. Outcome variables are body size, body composition and fat distribution, insulin sensitivity, lipid profile, blood pressure and autonomic regulation of cardiovascular function. Discussion This study will be one of the first population-based prospective cohort studies to address the association between measures of both prenatal and postnatal growth and various components of cardiovascular and metabolic function. Specific attention is paid to the timing of acceleration in growth and its potential association with the outcome variables. Importantly, the longitudinal design of this study gives us the opportunity to gain more insight into growth trajectories associated with adverse outcomes in later life. If identified as an independent risk factor, this provides further basis for the hypothesis that accelerated growth during the first years of life is a modifiable factor for the prevention of cardiovascular and metabolic disorders in later life. Moreover, identification of specific vulnerable periods during development may reveal suitable timeframes for early interventions.